Quantitative Trait Loci Analysis of Folate Content in Dry Beans, Phaseolus vulgaris L. - S. Khanal; J. Xue; R. Khanal; W. Xie; J. Shi; K. P. Pauls; A. Navabi (International Journal of Agronomy)
Dry beans (Phaseolus vulgaris L.) contain high levels of folates, yet the level of folate may vary among different genotypes. Folates are essential vitamins and folate deficiencies may lead to a number of health problems. Among the different forms of folates, 5-methyltetrahydrofolate (5MTHF) comprises more than 80% of the total folate in dry beans. The objectives of this paper were to compare selected genotypes of dry beans for the folate content of the dry seeds and to identify quantitative trait loci (QTL) associated with the folate content in a population derived from an inter-gene-pool cross of dry beans. The folate content was examined in three large-seeded (AC Elk, Redhawk, and Taylor) and one medium-seeded (Othello) dry bean genotypes, their six F1 (i.e., one-way diallel crosses), and the F2 of Othello/Redhawk that were evaluated in the field in 2009. Total folate and 5MTHF contents were measured twice with one-hour time interval. The significant variation (P<0.05) in the folate content was observed among the parental genotypes, their F1 progeny, and members of the F2 population, ranging from 147 to 345 μg/100 g. There was a reduction in the 5MTHF and total folate contents in the second compared to the first measurement. Dark red kidney variety Redhawk consistently had the highest and pinto Othello had the lowest total folate and 5MTHF contents in both measurements. A single marker QTL analysis identified three QTL for total folate and 5MTHF contents in the first measurement and one marker for the total folate in the second measurement in the F2. These QTL had significant dominance effects and individually accounted for 7.7% to 10.5% of the total phenotypic variance. The total phenotypic variance explained by the four QTL was 18% for 5MTHF and 19% for total folate in the first measurement, but only 8% for total folate in the second measurement.